2019
DOI: 10.1007/s00125-019-4842-0
|View full text |Cite
|
Sign up to set email alerts
|

A reduction in sedentary behaviour in obese women during pregnancy reduces neonatal adiposity: the DALI randomised controlled trial

Abstract: Aims/hypothesis Offspring of obese women are at increased risk of features of the metabolic syndrome, including obesity and diabetes. Lifestyle intervention in pregnancy might reduce adverse effects of maternal obesity on neonatal adiposity. Methods In the Vitamin D And Lifestyle Intervention for Gestational Diabetes Mellitus (GDM) Prevention (DALI) lifestyle trial, 436 women with a BMI ≥29 kg/m 2 were randomly assigned to counselling on healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 43 publications
4
71
1
Order By: Relevance
“…In both sexes, the early pregnancy period is relevant for neonatal adiposity, although for different metabolic parameters (ie, insulin resistance in boys and lipid levels in girls). Although a later intervention was effective in reducing neonatal adiposity, our data suggest that ideally maternal metabolism shall be normalized already early in pregnancy to reduce the risk of neonatal adiposity. Hence, interventions beginning prior to or in very early pregnancy might be even more effective than those initiated later, and achieved a 9% reduction in neonatal fat .…”
Section: Discussionmentioning
confidence: 69%
“…In both sexes, the early pregnancy period is relevant for neonatal adiposity, although for different metabolic parameters (ie, insulin resistance in boys and lipid levels in girls). Although a later intervention was effective in reducing neonatal adiposity, our data suggest that ideally maternal metabolism shall be normalized already early in pregnancy to reduce the risk of neonatal adiposity. Hence, interventions beginning prior to or in very early pregnancy might be even more effective than those initiated later, and achieved a 9% reduction in neonatal fat .…”
Section: Discussionmentioning
confidence: 69%
“…No other similar follow‐up studies have been published about the development of older children or about children's behavior and therefore we have no basis for comparison of these findings. Two lifestyle interventions during pregnancy in obese women that examined offspring anthropometrics, showed that the intervention reduced neonatal adiposity (van Poppel, Simmons, Devlieger et al ., ) and infant adiposity (Patel et al ., ). Conversely, other studies of prenatal lifestyle interventions showed no intervention effects on child anthropometrics or other early life metabolic risk factors (Ronnberg, Hanson & Nilsson, ; Tanvig, Vinter, Jorgensen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent RCT that included 334 neonates, counselling pregnant women with a BMI ≥29 kg/m 2 on both healthy eating and physical activity resulted in a significant reduction of neonatal adiposity (−63 g for fat mass, and −1.2% for fat percentage), although birth weight was not different between groups. Interestingly, these changes were not mediated by GWG alone, but a reduction in sedentary time (notably sitting time) drove the effect of the intervention on neonatal adiposity [38].…”
Section: Why Haven Lifestyle Interventions Not Achieved Better Outcommentioning
confidence: 95%